Uncommon presentation of postcardiac injury syndrome induced by radiofrequency catheter ablation for atrial fibrillation: Only pulmonary parenchymal inflammation - Han, Jie (J Cardiol Cases, 2016)
Postcardiac injury syndrome (PCIS) is characterized by the appearance of pericardial, pleural, or pulmonary parenchymal inflammation following a cardiac operation. The autoimmune disorder is characterized by eosinophilia, pleuritic chest pain, pleural, and pericardial effusion. It is a troublesome complication, which may prolong hospital stay and lead to severe and life-threatening conditions. Recently, its incidence appears to be declining, owing to modern immunomodulatory drug therapies. Here we report an uncommon case of PCIS, which occurred following a pulmonary vein isolation for atrial fibrillation. The patient suffered from pulmonary parenchymal inflammation but no pleuropericarditis after the operation. We describe with detailed clinical information, laboratory, and imaging tests, treatment processes, and a favorable prognosis in the content. This case illustrates that even after initially uneventful radiofrequency catheter ablation, careful, long-term follow-up is necessary to recognize the potential development of postcardiac injury syndrome. <Learning objective: Although uncommon, physicians should keep postcardiac injury syndrome in mind following radiofrequency catheter ablation. The pattern does not always resemble the classical picture described by Dressler, but may take many forms and should be sought. Diagnosis is based on the clinical signs and symptoms and is mostly confirmed after excluding other diseases. Prognosis is usually benign, and therapeutic response to anti-inflammatory drugs and corticosteroids can aid in the diagnosis.>